High Resolution Microbial Single Cell Analytics - Müller, Susann; Bley, Thomas (Advances in Biochemical Engineering/Biotechnology,, 2011)
Light Microscopic Analysis of Mitochondrial Heterogeneity in Cell Populations and Within Single Cells, by S. Jakobs, S. Stoldt, and D. Neumann *  Advanced Microscopy of Microbial Cells, by J. A. J. Haagensen, B. Regenberg, and C. Sternberg * Algebraic and Geometric Understanding of Cells, Epigenetic Inheritance of Phenotypes Between Generations, by K. Yasuda *  Measuring the Mechanical Properties of Single Microbial Cells, by C. R. Thomas, J. D. Stenson, and Z. Zhang *  Single Cell Analytics: Pushing the Limits of the Doable,         by H. Kortmann, L.M. Blank, and A. Schmid  * Cultivation-Independent Assessment of Bacterial Viability, by F. Hammes, M. Berney, and T. Egli *  Resolution of Natural Microbial Community Dynamics by Community Fingerprinting, Flow Cytometry and Trend Interpretation Analysis, by P. Bombach, T. Hübschmann, I. Fetzer, S. Kleinsteuber, R. Geyer, H. Harms, and S. Müller *Multivariate Data Analysis Methods for the Interpretation of  Microbial Flow Cytometric Data, by H.M. Davey, and C.L. Davey *  From Single Cells to Microbial Population Dynamics: Modelling in Biotechnology Based on Measurements of Individual Cells, by T. Bley.